Cardiac MRI and Echocardiography for Early Diagnosis of Cardiomyopathy Among Boys With Duchenne Muscular Dystrophy: A Cross-Sectional Study - Prakash, Nidhi; Suthar, Renu; Sihag, Bhupendra Kumar; Debi, Uma; Kumar, Rohit Manoj; Sankhyan, Naveen (Frontiers in Pediatrics, 2022)
Background: Cardiomyopathy is an important cause of morbidity and mortality in boys with Duchenne muscular dystrophy (DMD). Early diagnosis is a prerequisite for a timely institution of cardioprotective therapies in DMD related cardiomyopathy. Objective: We compared Cardiac MRI (CMRI) with transthoracic echocardiography (TTE) including Tissue Doppler Imaging (TDI), and Speckle Tracking echocardiography (STE) for diagnosis of cardiomyopathy in early ambulatory boys with DMD. Methodology: This cross-sectional study was conducted between June 2018 to December 2020. Consecutive boys between 7-15 years of age with DMD were enrolled. Percentage ejection fraction (EF), fractional shortening, wall motion abnormalities, early diastolic mitral annulus velocity (Ea), medial mitral annulus ratio (E/Ea), and global strain were measured with STE. CMRI derived EF, segmental hypokinesia, and late gadolinium enhancement (LGE) were studied and compared. Results: A total of 38 ambulatory boys with DMD were enrolled. The mean age was 8.8±1.6 years and none had clinical features related to cardiac dysfunction. In the TTE EF was ≤55% in 5(15%), FS was ≤28% in 3(9%), and one each had left ventricular wall thinning and wall hypokinesia. In TDI, none had diastolic dysfunction and STE showed reduced global strain <18% in 3(9%) boys. CMRI derived EF was ≤55% in 20(53%) boys and showed the presence of left ventricular wall hypokinesia in 9(24%) and LGE in 4 (11%) boys. Conclusion: Cardiomyopathy remains clinically asymptomatic among early ambulatory boys with DMD. A significantly higher percentage of boys revealed early features of DMD related cardiomyopathy in CMRI in comparison to echocardiography.